HISTORICAL ANALYSIS OF THE FORMATION OF THE CONCEPTUAL BASIS OF SUSTAINABLE DEVELOPMENT - YANOVSKA, Viktoriia; PARFENTIEVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article carried out a historical analysis of the process of emergence, formation and evolution of the conceptual foundations of sustainable development. The use of the historical method made it possible to reconstruct cause-and-effect relationships, recreate the events of the past and gain a deeper understanding of the content of the problems that preceded the emergence of the concept, identified the features of its formation and directed its consistent development. It has been found that ideas of sustainable development have a long history of dominance at the global societal level, spanning over fifty years. The adoption of the idea of sustainable development as the main one for humanity occurred as a result of the aggravation of environmental and social problems caused by the rapid growth of the total population of the planet and the growth of the global gross domestic product ahead of it, which was accompanied by the processes of globalization and was oriented towards the use of a development model focused on maximizing economic efficiency. The formation of the idea of sustainable development began with a dialogue between industrialized countries and developing countries regarding the connection between economic growth and environmental pollution and social well-being, as a result of which the concept and guiding principles of sustainable development were introduced, strategies for investing in the future were formed, a set of political commitments of states, innovative guiding principles of the green economy policy were adopted, a financing strategy was introduced, and sustainable development goals were adopted. In the process of global formation of ideological foundations, the content of sustainable development was defined as meeting the needs of the present without endangering the ability of future generations to meet their own needs.
Keywords: sustainable development; principles; goals of sustainable development; green economy; historical analysis; chronological sequence; cause-and-effect relationships